Comparative reflections upon the Assisted Dying Bill 2013: A plea for a more European approach. (June 2013) - Halliday, Samantha
Whilst assisted dying remains topical, a number of courts and committees have considered the potential legalisation of active voluntary euthanasia, and/or physician-assisted suicide, but concluded that legalisation should not occur. Significantly this conclusion is attributed not simply to concern to uphold the sanctity of life, but more commonly the reasons given stress that it would simply not be possible to legalise assisted dying whilst incorporating sufficient safeguards within the legislation to protect the vulnerable. This article considers the way in which the principle of dignity has been asserted to demand both that a person has a right to die with dignity (where dignity is constructed as entailing a choice to die with medical assistance) and that the prohibition of assisted dying be maintained in order to ensure the dignity of the person, regardless of whether that person is disabled or terminally ill. It assesses the validity of that argument by evaluating the safeguards incorporated into the Assisted Dying Bill 2013 and reflecting upon the experience of the statutory regulation of assisted dying in other jurisdictions: the Netherlands, Belgium and Oregon. It is concluded that it is possible to construct legislation authorising assisted dying in strictly controlled circumstances and that far from exposing the vulnerable to the risk of abuse, such regulation would provide much greater protection of all lives than the current system based upon an absolute prohibition of killing.